Empowering Learning Networks: Insights from Social Network Analysis in Inquiry-Based Discussions - Ayesha Sadaf; Larisa Olesova; Hajeen Choi (Online Learning)
This study investigated the dynamics of complex interactions within inquiry-based discussions by visualizing patterns using social network analysis. Researchers explored network measures when learners participated in inquiry-based discussions with Practical Inquiry Model (PIM) questions and non-PIM questions while playing the weekly moderator’s role. The findings revealed that at the group level, purposefully designed inquiry-based discussions can create fairly cohesive, evenly distributed, and proportionally consistent networks. Discussions featuring both PIM and non-PIM questions resulted in a moderate level of interaction, as learners adhered to the specified requirements for the number of responses. While discussions with non-PIM questions appeared more interactive with higher response requirements, discussions with PIM questions actually resulted in greater interaction, as evidenced by students exceeding the average number of required responses per student. The findings also revealed that despite similar discussion prompts and discussion requirements in both PIM and non-PIM, the flow of information can vary based on how closely learners are connected. At the individual level, the results revealed that learners' levels of participation, influence, and network positions fluctuated and shifted in each discussion. In addition, the results did not reveal any impact of the moderator's role on learner participation and interaction in discussions with both PIM and non-PIM questions. This study’s findings can help researchers and practitioners design a well-distributed network to enhance learner interaction in inquiry-based discussions with the balance of PIM and non-PIM questions.